Building blocks for sustainable transport : obstacles, trends, solutions - Perrels, A. H.; Himanen, Veli; Lee-Gosselin, Martin (Emerald Group Pub., 2008)
Argues that the issues surrounding sustainable transport constitute a new - post-modern - phase in transport policy and management. This book is organized into three sections that discuss a major set of challenges to the transition to a sustainable transport system.